The association of fatty acid desaturase gene polymorphisms on long-chain polyunsaturated fatty acid composition in Indonesian infants. Issue 5 (23rd November 2018) - Tanjung, Conny; Rzehak, Peter; Sudoyo, Herawati; Mansyur, Muchtaruddin; Munasir, Zakiudin; Immanuel, Suzanna; Irawan, Roedi; Reischl, Eva; Demmelmair, Hans; Hadinegoro, Sri Rezeki; Sjarif, Damayanti Rusli; Koletzko, Berthold
ABSTRACT: Background: Adequate availability of long-chain polyunsaturated fatty acids (LC-PUFAs) is important for human health from pregnancy to adulthood. Previous studies on fatty acid desaturase ( FADS ) gene single-nucleotide polymorphisms (SNPs) have been performed predominantly in Western populations and showed that FADS SNPs had a marked impact on LC-PUFA composition in blood and tissues. Objectives: We aimed to investigate the influence of fetal FADS genotypes on LC-PUFA composition in umbilical artery plasma lipids in Indonesian infants. Design: We performed a cross-sectional study to assess for these associations. Results: A total of 12 cord plasma n–6 (ω-6) and n–3 (ω-3) fatty acids were analyzed for associations with 18 FADS gene cluster SNPs from 390 women with single parturition from the Indonesian Prospective Study of Atopic Dermatitis in Infants (ISADI). Fetal FADS genotypes influenced cord plasma LC-PUFA composition, but, in contrast to previous studies from Western populations, the quantitatively predominant SNPs were associated with lower LC-PUFA content. Conclusion: To our knowledge, this study was the first in South East Asia on FADS genotypes and arterial cord blood fatty acids to show an association between fetal LC-PUFA composition and fetal FADS SNPs. The FADS genotype distribution differs markedly between different geographical populations. This trial was registered at clinicaltrials.gov as NCT02401178.